Identifikasi Kesalahan Mahasiswa dalam Menyelesaikan Soal Induksi Matematika pada Analisis Real: Perspektif Teori Kastolan - Fadilla, Nia; Andini, Putri; Masita, Nurul; Waniza, Elva; Sinaga, Sinta Marintan; Simanullang, Michael Christian (FKIP Universitas Mataram, 2025)
This study aims to identify and analyze the types of errors made by students in solving Mathematical Induction problems using Kastolan's theory. The analysis results are expected to clarify the specific difficulties faced by students and serve as a basis for improving the quality of mathematics education at the higher education level. This research employs a descriptive qualitative approach with ten sixth-semester students from the Mathematics Education Study Program at Universitas Negeri Medan as subjects. Data were collected through written tests, interviews, and documentation, and analyzed using the Miles and Huberman model, which includes data reduction, data display, and conclusion drawing. The results show that students made three main types of errors: procedural errors (50%), technical errors (27.27%), and conceptual errors (22.72%). Procedural errors were the most dominant, indicating a lack of understanding of the systematic steps required in inductive proofs. The primary cause of these errors was the students' insufficient comprehension of mathematical induction material during lectures. Therefore, a learning approach that emphasizes understanding logical structures and proof procedures is necessary to enhance the quality of mathematics instruction in higher education.